Análise da relação entre os fundos setoriais e a produtividade científica dos pesquisadores - Silva, Lizandra Duarte da (2018)
The objective of this study is to determine if there is a statistically significant relationship between the funding destined to CNPq through FNDCT sector funds, the main promoter of science, technology and innovation in Brazil, and the scientific production of the researchers registered in the Directory of Research Groups - DGP benefited from this funding, from 2003 to 2016. Specifically, the objective is to investigate the difference by Brazilian region, noting whether there is a concentration in resources and in scientific productivity and the trajectory of this difference over the analyzed period. Also, it investigates the difference by area of knowledge, observing in which the financing generates greater difference. Scientific productivity will be measured by the number of articles published in national and international journals. For this analysis will be made descriptive analyzes in absolute and proportional terms (weighting by the number of doctor researcher), Pearson correlations, in two periods, 2003 - 2016 and 2010 to 2016 and will be calculated the Coefficient of Williamson and Gini adapted. The results showed that, in proportional terms, there was no concentration of financing or scientific production among the Brazilian regions during the analyzed period, the inverse happens when one studies in absolute terms. It is concluded that there is evidence of a statistically significant relationship between the variables, however, only for publication in national journals and the results were not homogeneous. This positive relationship intensifies with the maturity of politics. It was demonstrated through the Williamson coefficient that the country showed a downward trend in the regional disparity of scientific production up to 2014 and that, concurrently with the reduction of FNDCT funding and scientific production, there was a tendency for the disparity to increase. By means of the Gini coefficient it was reinforced that there is a decentralization of the resources of the sectoral funds of the FNDCT. It is noteworthy that the large areas of knowledge and the Brazilian regions that received the largest amount of funding were the most productive. Finally, it is shown that the sectoral funds of the FNDCT are in crisis, can cause as a direct consequence the atrophy in the scientific development of the country.